2013
DOI: 10.5194/bg-10-8283-2013
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between substrate, surface characteristics, and vegetation in an initial ecosystem

Abstract: Abstract. We investigated surface and vegetation dynamics in the artificial initial ecosystem "Chicken Creek" (Lusatia, Germany) in the years 2006-2011 across a wide spectrum of empirical data. We scrutinized three overarching hypotheses concerning (1) the relations between initial geomorphological and substrate characteristics with surface structure and terrain properties, (2) the effects of the latter on the occurrence of grouped plant species, and (3) vegetation density effects on terrain surface change.Our… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…This finding indicates a temporal trend towards the spatial segregation of species according to soil properties. Similarly, Biber et al (2013) reported a significantly positive correlation between the species richness of N-fixing Fabaceae and the soil gravel content. Such findings contradict niche theories, which expect co-occurrences of functionally different species to increase synergistic effects (Silva and Batalha 2010) and to reduce possible interspecific competition (Götzenberger et al 2011).…”
Section: Discussionmentioning
confidence: 77%
“…This finding indicates a temporal trend towards the spatial segregation of species according to soil properties. Similarly, Biber et al (2013) reported a significantly positive correlation between the species richness of N-fixing Fabaceae and the soil gravel content. Such findings contradict niche theories, which expect co-occurrences of functionally different species to increase synergistic effects (Silva and Batalha 2010) and to reduce possible interspecific competition (Götzenberger et al 2011).…”
Section: Discussionmentioning
confidence: 77%
“…Hence, arresting further degradation and developing viable restoration methods are predominant concerns in the region. Forb, legume, and graminoid species are the main functional groups in natural grassland communities globally (Tilman et al, 2001;Stevens et al, 2004), but their proportions can also vary between and within ecosystems, biotopes and patches (Diaz et al, 2007;Biber et al, 2013;Tóth et al, 2016;Liu et al, 2017). In the Qinghai Tibetan Plateau, graminoid and legume species are rare in highly degraded grasslands, whereas graminoid and legume species are abundant in natural grassland (Wang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on the role of initial conditions in ESS development assume more homogeneous conditions in early stages, with increasing heterogeneity over time (Raab et al 2012;Biber et al 2013). Structural complexity for any form of divergence is greater than for a linear or cycle trend, as is graph irregularity.…”
Section: Alluvial Channelsmentioning
confidence: 99%
“…Biber et al (2013) study of interrelationships among substrate, topography, and vegetation in early stages of ESS development also assumed increasing complexity. Raab et al (2012) also noted the importance of historical information for understanding the contemporary state of an environmental system.…”
Section: Introductionmentioning
confidence: 99%